Mechanisms for the guarantee of programmatic voting in Colombia (2018)
The programmatic vote was a figure that was implemented after the issuance of the Political Constitution of Colombia of 1991, applicable for the territorial elections of governors and mayors, by means of which the citizens have the power to choose the most convenient proposals for their territory, and impose them as a mandate; However, in practice, government programs are relegated to the background, which is why the analysis of the mechanisms established for the effectiveness of the programmatic vote and the inadequacy of those mechanisms is important, since, in spite of the its institution and the different regulatory developments in this regard, there is no adequate application